2018
DOI: 10.1007/s11663-018-1372-y
|View full text |Cite
|
Sign up to set email alerts
|

Transient Rheological Behavior of Semisolid SEED-Processed 7075 Aluminum Alloys in Rapid Compression

Abstract: The transient rheological behavior and microstructure evolution of semisolid SEED-processed 7075 aluminum alloys were studied using the rapid compression tests. The effects of the TiB 2 grain refinement on the grain morphology and size of semisolid slurries were investigated. Results indicated that the grain refiner could reduce the grain size and improve the globularity of a-Al grains. The grain-refined alloy can be easily deformed at a wide range of solid contents (0.42 to 0.53 Fs), in which the deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Furthermore, as shown in Figure 10 , the microstructure of the semi-solid billets remains similar at different temperatures. This similarity contributes to the minimal variation in thixotropic behavior during the thixoforming process [ 38 ]. Therefore, the refined microstructure can be readily achieved across a wide range of solid fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as shown in Figure 10 , the microstructure of the semi-solid billets remains similar at different temperatures. This similarity contributes to the minimal variation in thixotropic behavior during the thixoforming process [ 38 ]. Therefore, the refined microstructure can be readily achieved across a wide range of solid fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of work concluded that fraction solid mainly affects the viscosity of the slurry, and the microstructure also has a significant effect on the rheological behavior. Bolouri and Silva [4,5] found the dendritic structure resulted in higher viscosity, and the viscosity of this kind of slurry is more sensitive to solid fraction compare to a globular structure. For semi-solid forming, the perfect morphology of the solid phase in the slurry is a spherical form, while it's tough to make the ideal slurry.…”
Section: Introductionmentioning
confidence: 96%
“…These slurries have a high solid fraction and are free of entrapped oxides, allow for the casting of heat-treatable and weldable components with high mechanical properties, high ductility, and ultra-low porosity. It is high-efficient on a wide variety of aluminium foundry alloys and has been demonstrated on wrought alloys, such as 6061 [4] and 7075 alloys [5]. The weights and dimensions of slurries can be adjusted according to the die casting system, and the process can be applied in both horizontal and vertical die/squeeze casting machines.…”
Section: Introductionmentioning
confidence: 99%